Methodology for estimating the effectiveness of an integrated information protection system for automated information systems of military management bodies - Валерій Олександрович Крайнов; Марина Федорівна Маланчук; Роман Іванович Грозовський (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The issue of information security is an important part of the concept of introducing new information technologies in military affairs. "The one who possesses reliable and complete information - the one who owns the situation, and the one who owns the situation - that is able to manage it in his own interests, and the one who is able to manage - that is able to win." Therefore, the protection of information in the information environment of military command and control agencies is currently a very urgent problem that needs to be addressed.